Identification of LTBP2 gene polymorphisms and their association with thoracolumbar vertebrae number, body size, and carcass traits in Dezhou donkeys - Liu, Ziwen; Wang, Tianqi; Shi, Xiaoyuan; Wang, Xinrui; Ren, Wei; Huang, Bingjian; Wang, Changfa (Frontiers in Genetics, 2022)
The number of thoracolumbar vertebrae in Dezhou donkey varies from 22 to 24 and is associated with body size and carcass traits. In mammals, Latent transforming growth factor beta binding protein 2 (LTBP2) has been found have some functions in the development of thoracolumbar vertebrae. The relationship between LTBP2 and TLN of Dezhou donkeys is yet reported. The purposes of this study are as follows: (a) Quantifying the effect of thoracolumbar number variation of Dezhou donkey; (b) Studying the distribution of single nucleotide variants (SNVs) in LTBP2 gene of Dezhou donkey; (c) Exploring whether these SNVs can be used as candidate sites to study the mechanism of Dezhou donkey muti-thoracolumbar vertebrae development. The TLN, body size and carcass traits of 392 individuals from a Dezhou donkey breed were recorded. All animals were sequenced for LTBP2 by GBTS Liquid chip and 16 SNVs were used for further analysis. We then analyzed the relationship between these SNVs with TLN, body size and carcass traits. The results showed that c.5547+860 C > T, c.5251+281 A > C, c.3769+40 C > T, and c.2782+3975 A > G were complete genetic linkage and significantly associated with thoracic number (TN) (P < 0.05), wild-type homozygotes had more TN than heterozygotes, c.1381+768 T > G and c.1381+763 G > T were significantly associated with lumber vertebrae (LN) (P < 0.05), c.1003+704 C > T, c.1003+651 C > T, c.1003+626 A > G and c.812+22526 T > G were significantly associated with chest circumference (CHC), front carcass weight (CWF), after carcass weight (CWA) and carcass weight (CW) (P < 0.05), wild-type homozygotes were larger than other genotypes in CHC, CWF, CWA and CW. The effect of variation is not consistent in c.565+11921 A > G, c.565+6840 A > G, c.565+3453 C > T and c.494+5808 C > T. These results provide useful information that the polymorphism of LTBP2 is significantly associated with TLN, body size and carcass traits in Dezhou donkey, which can serve as a molecule marker to improve donkey production performance.